THE EFFECT OF FRAUD PENTAGON ON FRAUDULENT FINANCIAL STATEMENTS: A META ANALYSIS - Hernadi, Kezia Natalie; Meiden, Carmel (Journal of International Conference Proceedings, 2023)
This study aims to integrate research results from several journals to ascertain the impact of financial statement fraud (FFS) on fraud pentagon. FFS is an intentional effort by the company to mislead users of financial statements. Fraud pentagon explains the five elements causing FFS. The population in this study is a journal which not included in predatory journal for 2012-2022. There are 16 samples produced through purposive sampling. Secondary data for meta analysis techniques is produced through observation techniques in Seforra and Google Scholar. The results of integration show that the pressure, opportunity, capability and arrogance have positive effect on FFS as evidenced through (ṝ) calculating > r table. While the rationalization variable has a negative effect on fraud financial statements.